Textbook of work physiology: Physiological bases of exercise - Åstrand, Per-Olof; Rodahl, Kåre (New York McGraw - Hill, 1977)
Textbook of work physiology is the same as that of the original text: to bring together into one volume the various factors affecting human physical performance in a manner that is comprehensible to the conventional textbooks of physiology, in which the emphasis is on the regulation of the various function of the body at rest, the regulatory mechanisms studied during physical activity have been especially emphasized in this book.
Keywords: Y Đa khoa